Meta-Synthesis: The Effect of Problem-Based Learning Model on Students’ Mathematical Connection Ability - Syifaa’ Nurhidayah; Putriaji Hendikawati; Scolastika Mariani; Isnaini Rosyida (EduMa: Mathematics education learning and teaching, 2025)
Mathematical connection ability plays a crucial role in enabling students to understand relationships among mathematical concepts, apply mathematical ideas in real-life contexts, and develop higher-order thinking skills. However, evidence from the field indicates that students’ mathematical connection ability remains relatively low due to instructional practices that emphasize procedural mastery rather than conceptual understanding. This study aims to analyze the effect of the Problem-Based Learning (PBL) model on students’ mathematical connection ability through a meta-synthesis approach. The meta-synthesis reviewed six primary research articles selected systematically from Google Scholar, ERIC, and reputable national and international journals published between 2020 and 2025. The findings reveal that PBL consistently enhances students’ mathematical connection ability through contextual problem-solving activities, the use of visual representations and learning media, and collaborative reflection. These results indicate that PBL is an effective instructional model for strengthening students’ mathematical connections in a meaningful and applicable learning environment.